Vibrio cholerae Skin and Soft Tissue Infection Complicated by Sepsis in an Immunocompromised Patient: A Rare Case Report - Erin Rebecca Carr; Adrian Estepa; Jordan Colson; Folusakin Ayoade (Clinical Case Reports)
ABSTRACT Physicians should consider non‐O1, non‐O139 Vibrio cholerae (NOVC) in the differential diagnosis of cellulitis complicated by sepsis, especially in immunocompromised patients when potential exposure exists. Due to the pathogen's potential for severe infections and rising incidence from environmental changes, we emphasize the need for increased awareness and appropriate treatment guidelines.